KESIAPAN GURU SD dalam TRANSFORMASI DIGITAL: ANALISIS PELATIHAN, INOVASI, dan TANTANGAN IMPLEMENTASI di KAPANEWON BANGUNTAPAN - Jeni Hartanti; Akbar Al Masjid; Ana Fitrotun Nisa; Berliana Henu Cahyani; Elyas Djufri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
ABSTRACT This study aims to analyze the relationship between digital training, teacher innovation, and the challenges of implementing digital platforms among elementary school teachers in Kapanewon Banguntapan, Bantul Regency. The advancement of technology in the Education 5.0 era requires teachers to adapt to digital-based learning, although limitations such as infrastructure, digital literacy, and institutional support remain obstacles. The study employed a quantitative approach with a descriptive survey method. The sample consisted of 22 elementary school teachers selected through purposive sampling. The research instrument used a Likert-scale questionnaire (1–5) encompassing three main variables: digital training (X₁), teacher innovation (X₂), and implementation challenges (Y). Data were analyzed using Jamovi through reliability tests, descriptive statistics, and Pearson correlation. Simulated results indicated that all variables had high reliability (α > 0.8). Descriptive results showed that digital training (M = 4.23, SD = 0.45) and teacher innovation (M = 4.10, SD = 0.52) were in the high category, while implementation challenges (M = 2.91, SD = 0.60) were in the low category. Pearson’s correlation analysis revealed a significant positive relationship between digital training and teacher innovation (r = 0.56, p < 0.01) and a significant negative relationship between digital training and implementation challenges (r = –0.42, p < 0.05). These findings highlight the importance of continuous digital training to enhance innovation and reduce barriers in technology based learning. Keywords: digital training, teacher innovation, implementation challenges, digital platform, elementary education ABSTRAK Penelitian ini bertujuan untuk menganalisis hubungan antara pelatihan digital, inovasi guru, dan tantangan implementasi platform digital pada guru sekolah dasar di Kapanewon Banguntapan, Kabupaten Bantul. Kemajuan teknologi di era Pendidikan 5.0 menuntut guru untuk beradaptasi dengan pembelajaran berbasis digital. Namun, masih terdapat kendala seperti keterbatasan sarana, literasi digital, dan dukungan institusional. Penelitian ini menggunakan pendekatan kuantitatif dengan metode survei deskriptif. Sampel penelitian terdiri atas 25 guru sekolah dasar yang dipilih secara purposive. Instrumen penelitian menggunakan angket skala Likert 1–5, mencakup tiga variabel utama: pelatihan digital (X₁), inovasi guru (X₂), dan tantangan implementasi (Y). Data dianalisis menggunakan aplikasi Jamovi melalui uji reliabilitas, analisis deskriptif, dan korelasi Pearson. Hasil simulasi menunjukkan bahwa semua variabel memiliki reliabilitas tinggi (α > 0,8). Secara deskriptif, pelatihan digital (M = 4,23; SD = 0,45) dan inovasi guru (M = 4,10; SD = 0,52) berada pada kategori tinggi, sedangkan tantangan implementasi (M = 2,91; SD = 0,60) berada pada kategori rendah. Analisis korelasi menunjukkan hubungan positif signifikan antara pelatihan digital dan inovasi guru (r = 0,56, p < 0,01) serta hubungan negatif signifikan antara pelatihan digital dan tantangan implementasi (r = –0,42, p < 0,05). Hasil ini menegaskan pentingnya pelatihan digital berkelanjutan untuk meningkatkan inovasi dan mengurangi hambatan guru dalam penggunaan teknologi pembelajaran. Kata Kunci: pelatihan digital, inovasi guru, tantangan implementasi, platform digital, pendidikan dasar